Faktor Yang Berhubungan Dengan Kejadian Pneumonia Pada Balita Di Rumah Sakit TK II Pelamonia Makassar (Window of Public Health Journal, 2026)
Pneumonia is an acute respiratory infection that attacks the lungs. The lungs consist of small sacs called alveoli, which fill with air when a healthy person breathes. This study aims to determine the factors associated with pneumonia incidence among toddlers at the Makassar Class II Pneumonia Hospital. The research design is quantitative and cross-sectional. The study population consisted of 96 respondents. The sample calculation used the Lemešow formula, yielding a sample of 77 respondents. The instrument used was a questionnaire. Data analysis used univariate and bivariate analysis. The analyzed data are presented in tabular form, followed by a narrative explanation. The results of the study showed that there was a relationship between nutritional status and the incidence of pneumonia in toddlers, namely (p = 0.000